Penerapan Aquaponik di Lahan Pekarangan Rumah untuk Tercapainya SDGs Desa Tanpa Kelaparan di Desa Taba Jambu - Ratu Eva Febriani; Roosemarina Anggraini Rambe; Merri Anitasari (UNIB Press, 2022)
The increasing population with limited carrying capacity raises crucial problems. Currently the problem of food insecurity is one of the focuses of the government in Indonesia so that it is included in one of the SDGs programs. Taba Jambu Village is a village that borders the City of Bengkulu, so its strategic location has resulted in the conversion of land into housing and shops. For the long term, a food safety net needs to be prepared through the application of a cropping pattern in the form of Aquaponics.